Dietary Intake Patterns and Diet Quality in a Nationally Representative Sample of Women With and Without Severe Headache or Migraine. Issue 4 (11th March 2015) - Evans, E. Whitney; Lipton, Richard B.; Peterlin, B. Lee; Raynor, Hollie A.; Thomas, J. Graham; O'Leary, Kevin C.; Pavlovic, Jelena; Wing, Rena R.; Bond, Dale S.
<x xml:space="preserve">Abstract</x> Objective/Background The role of diet in migraine is not well understood. We sought to characterize usual dietary intake patterns and diet quality in a nationally representative sample of women with and without severe headache or migraine. We also examined whether the relationship between migraine and diet differs by weight status. Methods In this analysis, women with migraine or severe headache status was determined by questionnaire for 3069 women, ages 20‐50 years, who participated in the National Health and Nutrition Examination Study, 1999‐2004. Women who experienced severe headaches or migraines were classified as migraine for the purposes of this analysis. Dietary intake patterns (micro‐ and macronutrient intake and eating frequency) and diet quality, measured by the Healthy Eating Index, 2005, were determined using one 24‐hour dietary recall. Results Dietary intake patterns did not significantly differ between women with and without migraine. Normal weight women with migraine had significantly lower diet quality (Healthy Eating Index, 2005 total scores) than women without migraine (52.5 ± 0.9 vs 45.9 ± 1.0; P < .0001). Conclusions Whereas findings suggest no differences in dietary intake patterns among women with and without migraine, dietary quality differs by migraine status in normal weight women. Prospective analyses are needed to establish how diet relates to migraine onset, characteristics, and clinical features in individuals of varying weight status.